ANÁLISE DE IMPACTOS AMBIENTAIS E TOPOLOGIA EM PROJETO ÓTIMO DE TRELIÇAS MISTAS DE AÇO E CONCRETO VITÓRIA 2022 - Klein, Diego (2022)
The civil construction sector is one of the main responsible for the emission of CO2 into the atmosphere, mainly with regard to the manufacture of construction materials, which is why the search for structural solutions with less environmental impact has been a constant object of research in the area. In Brazil, the use of composite steel and concrete structures has grown significantly in recent decades due to factors such as resource rationalization, structure weight reduction and faster construction. In addition, given the competitiveness that the structural model of flat truss presents in relation to medium and large spans, it is necessary to expand the scope of research related to the design, verification and optimization of composite steel and concrete trusses. Thus, in this work, it was proposed the optimization of CO2 emission, via Genetic Algorithm (GA) and the Particle Dispersion Algorithm (PSO), of mixed steel and concrete trusses with tubular steel profiles considering topology variation (layout of the truss panels) and whether or not to fill the upper flange profile with concrete. The analyzes were carried out for the three most common truss models: Pratt, Howe and Warren. The dimensions of the profiles, the compressive strength of the slab concrete and the concrete filling the upper flange, the number of panels, the height of the truss and the choice of slab shape were considered as design variables. Numerical examples were evaluated to verify which are the elements that most impact the final CO2 emission of the structure, in addition to evaluating the effectiveness of the algorithms to obtain the optimal solution and the impacts on the final optimization when considering the concrete filling in the upper flange tube. . An analysis of the structure's collapse modes was carried out in order to verify which are the governing constraints of the problem. The results indicate that there is a reduction in the final emissions of the structure when the upper flange tube is filled in. Although it increases the final emission of the concrete, there is a considerable reduction of steel in the upper flange profile.